PRESTASI PENERAPAN FUZZY MAMDANI DALAM PENENTUAN PRESTASI BELAJAR SISWA STUDY KASUS: SMK NEGERI 1 SERGAI - Vinsensia, Desi (Sinkron : jurnal dan penelitian teknik informatika, 2018)
This research applies Fuzzy Logic Mamdani in determining student achievement by taking case study SMK NEGERI 1 Serdang Bedagai. In this case there are 3 variables that become inputs: visual learning style, auditorial learning style, and kinesthetic learning style. Output is the result of learning achievement. Fuzzy mamdani can be one tool in determining student achievement, in this study using MATLAB 6.1